2012
DOI: 10.1007/s00167-012-2059-6
|View full text |Cite
|
Sign up to set email alerts
|

Significant effect of the posterior tibial slope and medial/lateral ligament balance on knee flexion in total knee arthroplasty

Abstract: Purpose The intra‐operative femorotibial joint gap and ligament balance, the predictors affecting these gaps and their balances, as well as the postoperative knee flexion, were examined. These factors were assessed radiographically after a posterior cruciate‐retaining total knee arthroplasty (TKA). The posterior condylar offset and posterior tibial slope have been reported as the most important intra‐operative factors affecting cruciate‐retaining‐type TKAs. The joint gap and balance have not been investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 43 publications
(68 reference statements)
0
48
0
Order By: Relevance
“…Measurements of soft-tissue balance were performed only with 40 lb of distraction force throughout ROM. Asano et al evaluated stiffness of the softtissue complex in osteoarthritic knees in PS and showed that stiffness in extension was significantly greater than that in flexion [36]. Different distraction forces may lead to different soft-tissue balance, which may result in different operative procedures and postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of soft-tissue balance were performed only with 40 lb of distraction force throughout ROM. Asano et al evaluated stiffness of the softtissue complex in osteoarthritic knees in PS and showed that stiffness in extension was significantly greater than that in flexion [36]. Different distraction forces may lead to different soft-tissue balance, which may result in different operative procedures and postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the postoperative flexion angle and the amount of increase therein with regard to changes in the PCO, PSA, and JLH were analyzed (Pearson's correlation analysis) 2) . Knees showing postoperative PCO reduction within 3 mm of the preoperative value were assigned to the inlier group (PCO-inlier, n=111).…”
Section: Methodsmentioning
confidence: 99%
“…The range of flexion after TKA is probably influenced by many factors, including patient factors, prosthesis design, surgical technique, and rehabilitation. In terms of patient factors, the preoperative flexion angle is known to greatly influence the postoperative flexion angle 1 2) . In terms of surgical factors, changes in the femoral posterior condylar offset (PCO), tibial posterior slope angle (PSA), joint line height (JLH), femoral roll back, posterior cruciate ligament (PCL) tension, gap balancing, and patellar tracking have been analyzed 3 4 5 6 7 8) .…”
Section: Introductionmentioning
confidence: 99%
“…So the positioning of the tibial component has more influence on knee kinematics after UKA implantation. The role of the tibial slope in knee surgery has gained a lot of attention in total knee arthroplasty and in high tibial osteotomy (Bellemans et al, 2005;Fujimoto et al, 2012;Jojima et al, 2004).…”
Section: Introductionmentioning
confidence: 99%